Ekklesiologie der sanften Macht. Der 1. Timotheusbrief und die antike Fürstenspiegel-Literatur - Becker, Matthias (Biblische Zeitschrift, 2020)
Did early Christian church leaders and political rulers share common characteristics? By reading the First Epistle to Timothy through the lens of Greek and Roman “mirrors for princes” (specula principum) written in the first and early second centuries AD, this article intends to make a new contribution to this issue. The study’s interpretative focus lies on the idealized depiction of Timothy as a role model for early Christian officeholders as well as on the qualifications for bishops and deacons (1 Tim 3:1-13). The comparison of the features of the ideal ruler with those of ideal church leaders shows that central elements of the ecclesiology of First Timothy tap into the Greco-Roman discourse concerning ideal rulership. Yet not only that, it also helps to understand that the power that is undeniably attributed to officeholders is ultimately meant to be a soft power that serves the cause of “preservation” and “salvation” (σωτηρία).